Diplomacy and Highpoints in the Historical Development of Nigeria–Saudi Arabia Affinities: A Study in Afro-Arab Relations - JABO, Sahabi Maidamma; UBANDAWAKI, Umar (Socialscientia: Journal of Social Sciences and Humanities, 2021)
Nigeria and Saudi Arabia are two important countries in the socio-economic and political activities in their respective regions. In Africa, Nigeria plays a key role in socio-economic, political and cultural development of the continent. This is evident by its contribution to mediations, peace keeping operations in Africa and other parts of the World. This is also demonstrated in its role of being one of the founders of the Economic Community of West African States (ECOWAS), Organization of African Unity (O.A.U.) now African Union (A.U). Equally, Saudi Arabia plays important role in the politics of the Middle East, essentially, as it relate to Regional Security, Arab Nationalism and Islam. In view of this, the study examines the genesis of Nigeria-Saudi Arabia diplomatic relations. The paper also explores factors that were responsible for the establishment and continuity of the relations between the two countries. Information gathered from books and some documentary sources, including official files were subjected to content analysis. The paper found out that religion (Islam) and arabization were the fundamental factors that played key role in establishing diplomatic relations between Nigeria and Saudi Arabia. Equally, the paper found out that presence of Nigerian illegal immigrants in Saudi Arabia, arrest, detentions and executions of Nigerians by the Saudi Arabian authorities were the causes of diplomatic strains between the two countries. The paper recommends that even for protection of Nigeria’s image, the Nigerian government should take measures to curtail the inflow of Nigerian illegal immigrants into Saudi Arabia.